Faktor-faktor yang Memengaruhi Preferensi Nasabah terhadap Produk Rahn: Studi Kasus PT. BPRS Amanah Ummah - Lisda Qotrunnada Nabila Putri; Jaenal Effendi (Department of Islamic Economics, IPB University, 2020)
Rahn is financing for the community to borrow money using personal items as collateral. Public interest in rahn is still small, even though rahn knew as savings and loan services for property that is guaranteed by customers. The savings and loan services are paid every month along with the loan installments and do not use the interest system, only determining the nominal value of the rupiah determined by the pawning party. Thus, this study aims to determine the factors that influence customer preferences in choosing rahn products. The total of 120 respondents are taken, with a proportion of 60 as respondents representing rahn product respondents and 60 other respondents. The collected data is processed using logistic regression techniques. The results of the study show the factors that influence customer preferences for rahn products are factors of knowledge, promotion, service, education level, employment, income, expenditure and the number of dependents significantly influence customer decisions in choosing rahn products.